The E.M.M.A. effect : a novel - Riley, Lia (Avon, 2025)
Jane Austen meets Ali Hazelwood in this steamy, friends-to-lovers, STEM rom-com! He's her best friend's little brother and NHL forward. She's a computer scientist used to being in control. The E.M.M.A., her elite AI training program, claims optimizing his performance requires one thing: the perfect match. According to its calculations, that's her... Will Harriet discover that The E.M.M.A. knows best?